2023
DOI: 10.4018/ijec.316828
|View full text |Cite
|
Sign up to set email alerts
|

Reform of English Writing Teaching Method Under the Background of Big Data and Artificial Intelligence

Abstract: In the new era of informatization, big data, and artificial intelligence, the education field has also set off a wave of informatization development of English education. Teaching writing has always been the focus and challenge of English teaching, but there are various problems in English writing teaching in China. Problems such as difficulty in writing, vague expression, unclear main points, simple sentence structure, low vocabulary, etc. How to effectively carry out English writing teaching courses is worth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…The traditional approach to teaching AW, which often involves lectures and individual writing assignments, is ineffective in enhancing students' AW skills. The teaching of writing skills in the Chinese context is a challenging job because it incorporates various skills from drafting to the final essay (Chen, 2023). The findings of the study reported students' difficulties in writing since they used vague expressions, unclear main points, and simple sentence structure as a result of low vocabulary and organization knowledge.…”
Section: Problem Statementmentioning
confidence: 91%
“…The traditional approach to teaching AW, which often involves lectures and individual writing assignments, is ineffective in enhancing students' AW skills. The teaching of writing skills in the Chinese context is a challenging job because it incorporates various skills from drafting to the final essay (Chen, 2023). The findings of the study reported students' difficulties in writing since they used vague expressions, unclear main points, and simple sentence structure as a result of low vocabulary and organization knowledge.…”
Section: Problem Statementmentioning
confidence: 91%
“…The education process is an interactive process, which is embodied in three aspects, namely, the interaction between teachers and students in education and learning, the interaction between students in learning and discussing, and the interaction between teachers in discussing a topic together (Chen & Chen, 2022). Courseware is a kind of education system that includes all kinds of information in education and its processing.…”
Section: Methodology Multimedia Courseware-making Course Based On Net...mentioning
confidence: 99%
“…In fact, most of the knowledge and experience of education experts are concentrated in classroom education. Therefore, most of their knowledge and experience are transformed into courseware libraries in modern distance education resource library (Chen, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…English teaching activities are a complex and diverse process, which contains a variety of uncertain human factors, and artificial intelligence has the simulation of human thinking patterns and the reproduction of the thinking solution reasoning process as its most prominent features, so the complexity shown in the process of teaching English must be targeted by artificial intelligence for targeted solutions so that each learner can receive The complexity of the English language teaching process must be addressed by artificial intelligence so that each learner can receive personalized support and guidance. [3] Since "listening" and "speaking" are important components of elementary English teaching, adding AI as a cutting-edge technology to elementary English classroom teaching can greatly improve the quality of elementary English teaching. For example, teachers can use artificial intelligence systems in elementary school listening English listening exercises.…”
Section: The Relationship Between Artificial Intelligence and English...mentioning
confidence: 99%